Efektivitas Bahan Ajar Buku "Panduan Pembelajaran Kebencanaan Kabupaten Klaten" Pada Bencana Angin Badai Melalui Strategi Card Sort Di SMA N 1 Karanganom - Marsudi, Marsudi; , Dra. Siti Taurot Aly, M.Pd (2016)
This research aims to (1) identify the increasse of student learning outcome after disaster learning use the guiding book of disaster guidance of Klaten Regency through Card Sort strategy, (2) identify the efektivity of the book of "disaster learning guidance of klaten regency" on sudden storm material through card sort strategy in disaster learning to students who join extracuriccular of Sekolah Siaga Bencana in SMA N 1 Karanganom.type of this research is kuantitatif research. This research use experiment by using pretest-postest control group design. In collecting the data, the researcher use observation, test, and document. Technique of anayitic regulations test in this research areinstrument validity test, instrument reability test, normality test, hypothesis test. In analyzing the data, the researcher use learning outcome analysis and comparing experiment class and control class. Based on the research, the researcher conclude that (1) in normality test, the result shows significant value is 0,00 so it can be known that the spread of learning outcome before and after learning process use card sort strategy by doing wilcoxon test and mann whitney test to identify the differences of learning outcome between experiment class and control class. The result of wilccoxon test shows significant value is 0,00<0,05 so based on the result of the test, there are the distinction before and after learning by using sort card strategy. The result of mann whiteney test shows significant value 0,00<0,05 so there is no significant distinction between experiment class and control class. (2) there is the raising learning outcome in both of experiment class and control class before and after learning. The comparison of the student learning outcome before and after learning was done without stragy but just use conventional strategy i.e. talk. Before learning was done, the average of student score shows 44,1 and after learning process by using konventional method to the students in control class, the average of student score increase to 73,1. This result shows there is the raising of the students score average in control class before and after learning by using konventional method and the raising of the value is 29,97. (3) the result of this research can be implemented in geographic learning in X grades of Senior High School based on KI.1. "understand the context of readiness and disaster mitigation because of combination factor "nature and human act". Beside that this research is also appropiate with KD 1.1. "explain various kind of disaster risk in klaten regency.